Tuberculosis and survival in past populations: A paleo-epidemiological appraisal. (June 2015) - Blondiaux, Joël; de Broucker, Amélie; Colard, Thomas; Haque, Azizul; Naji, Stephan
Summary: Historical assessments of the last two centuries consistently placed tuberculosis as the leading cause of mortality. However, for earlier periods, we can only calculate the frequencies of archaeological bone lesions, which tell us little about the real impact of the disease on mortality. These lesions are usually observed in individuals who have developed immune resistance, which is visible as healed osteo-articular lesions. This study aimed to test the differential impacts of tuberculosis, cribra orbitalia and cribra femoris on adult survival and sex-based survival. We analyzed 28 French adult samples from the Antiquity and the Early Middle Ages. The age-at-death of 1480 individuals was estimated using cementochronology. Survival curves and median age-at-death were calculated to test new hypotheses that challenge the parasitic and deficiency theories of bone stress markers. Comparisons between carriers and non-carriers provided new information concerning the plausible causes of bone stress markers related to infections and TB. The most likely hypothesis is skeletal demineralization and osteoclastic resorption, which are usually observed close to tubercular granuloma or distant from active lesions. The bone marrow niche of Mycobacterium tuberculosis within CD271 + BM-MSCs stem cells is the proposed explanation for the localized cortical resorption that is observed in bone stress markers.